2014
DOI: 10.15420/aer.2014.3.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cost-effectiveness of Catheter Ablation of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is one of the most common cardiac conditions treated in primary care and specialty cardiology settings, and is associated with considerable morbidity, mortality and cost. Catheter ablation, typically by electrically isolating the pulmonary veins and surrounding tissue, is more effective at maintaining sinus rhythm than conventional antiarrhythmic drug therapy and is now recommended as first-line therapy. From a value standpoint, the cost-effectiveness of ablation must incorporate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…We therefore elected only to model VT storm—this was taken to put the patient into the readmission health state of our model. Thus, rather than relying on significant use of expert opinion to infer utilities performed in previous studies,10 14 we included only health states with patient-reported utilities supported by verifiable objective data. This is an important distinction as the objectivity of expert opinion by interested parties is difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore elected only to model VT storm—this was taken to put the patient into the readmission health state of our model. Thus, rather than relying on significant use of expert opinion to infer utilities performed in previous studies,10 14 we included only health states with patient-reported utilities supported by verifiable objective data. This is an important distinction as the objectivity of expert opinion by interested parties is difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…To account for recurrent clinical events, a Markov model instead of a decision tree was employed to simulate a hypothetical cohort of 1000 patients undergoing a VT ablation strategy and 1000 patients undergoing an AAD strategy. Following previous modelling studies in catheter ablation,10 14 we considered a 5-year time horizon for the base-case analysis, striking a balance between clinical relevance and available evidence on long-term cost and outcomes in this population. Scenarios with both a 10-year and lifetime horizon were considered in sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The reported costs of catheter ablation for AF have been observed to have significant variations, even within the same country [ 35 ]. While hospital billing records report that the cost of catheter ablation for AF is $17,173 in the U.S., government reports indicate that the cost of catheter ablation in the U.S. is $26,584 [ 15 , 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…The reported costs of catheter ablation for AF have been observed to have significant variations, even within the same country [ 35 ]. While hospital billing records report that the cost of catheter ablation for AF is $17,173 in the U.S., government reports indicate that the cost of catheter ablation in the U.S. is $26,584 [ 15 , 35 ]. A recent study estimated that the cost for AF ablations that used CARTO/3D, non-CARTO/non-3D mapping, and NAVx systems had a range between $16,278 and $21,294; other studies reported costs of AF ablation ranging from $14,000 to $18,000 [ 28 , 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…AF is a common arrhythmia in clinical practice, with a prevalence of 2.7 million–6.1 million that is expected to rise to 5.6 million–12 million by 2050 in the US alone. [ 1 , 2 ] Patients with AF have an increased risk of stroke and mortality and a decreased quality of life. [ 3 ] In addition, management of AF increases the cost of healthcare.…”
mentioning
confidence: 99%